1975
DOI: 10.1007/bf02205232
|View full text |Cite
|
Sign up to set email alerts
|

Classification and biological distribution of histamine receptor sub-types

Abstract: The distribution and classification of histamine receptors in mammalian and avian tissues have been summarized in Tables 1-4. It is evident that histamine receptors are present on a number of morphologically distinct cell types and the proportion of cells bearing H1- and H2-receptors varies not only with the species but also with the cell source. The pharmacological receptors mediating mepyramine-sensitive histamine responses have been defined as H1-receptors. Receptors mediating mepyramine-resistant, but buri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(44 citation statements)
references
References 138 publications
2
41
0
Order By: Relevance
“…For example, in the rabbit airway, the potassium (128 mm K)-and histamine (10pM)-induced contractions in the trachea are much smaller than the acetylcholine (ACh, 10 M)-induced contraction, but in the third branch of the right middle bronchial tree, these same three stimulants generate much the same amplitude of contraction and, moreover, the amplitude of the ACh-induced contraction is larger than that observed in the trachea (Fujiwara et al, 1988). In the guinea-pig, dog, bovine and rabbit tracheal and bronchial tissues, histamine produces contraction by stimulation of the Hl-receptor, though H2-receptors are also present (Chand & Eyre, 1975;Kirkpatrick, 1975;Kotlikoff et al, 1987). Ito & Tajima (1982) demonstrated that in the dog trachea, isoprenaline produces hyperpolarization of the membrane, reduces the resting tone and relaxes tissues precontracted by ACh.…”
Section: Introductionmentioning
confidence: 88%
“…For example, in the rabbit airway, the potassium (128 mm K)-and histamine (10pM)-induced contractions in the trachea are much smaller than the acetylcholine (ACh, 10 M)-induced contraction, but in the third branch of the right middle bronchial tree, these same three stimulants generate much the same amplitude of contraction and, moreover, the amplitude of the ACh-induced contraction is larger than that observed in the trachea (Fujiwara et al, 1988). In the guinea-pig, dog, bovine and rabbit tracheal and bronchial tissues, histamine produces contraction by stimulation of the Hl-receptor, though H2-receptors are also present (Chand & Eyre, 1975;Kirkpatrick, 1975;Kotlikoff et al, 1987). Ito & Tajima (1982) demonstrated that in the dog trachea, isoprenaline produces hyperpolarization of the membrane, reduces the resting tone and relaxes tissues precontracted by ACh.…”
Section: Introductionmentioning
confidence: 88%
“…As opposed to the goat trachea (this study), several well-known D-and M-tryptamine receptor antagonists have been reported to be ineffective in antagonizing 5-HT-induced contractions of cat trachea (Statkov, 1969) and relaxations of sheep pulmonary vein (Eyre, 1975).…”
Section: Discussionmentioning
confidence: 60%
“…After HI-receptor blockade, 4-methylhistamine and dimaprit (relatively selective H2-agonists) (Chand & Eyre, 1975; Owen, Ganellin & Durant, 1977) relaxed goat trachea. Cimetidine and metiamide (H2-antagonists) (Chand & Eyre, 1975) weakly enhanced histamine-induced contractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since no analysis of the different histamine receptor expression was performed in lung tissue in the present study the discussion about H 3 and H 4 remains speculative and is a clear limitation of this study. Normally, in the lungs histamine acts on H 1 -and H 2 -receptors and its effect is therefore balanced by the H 1 -mediated contraction and the H 2 -mediated relaxation of airway smooth muscles [42][43][44][45]. The observation that histamine contracts tracheal and bronchial airways, but relaxes smaller bronchi and bronchioles [46], indicates that there is a shift towards predominance of H 2 2receptors towards the peripheral airways.…”
Section: Discussionmentioning
confidence: 99%